2017
DOI: 10.1016/s2352-4642(17)30044-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes in youths: mechanisms and biomarkers

Abstract: Obesity has been estimated to decrease life expectancy by as little as 0.8 to as much as 7 years being the second leading cause of preventable death in the United States after smoking. Along with the increase in the prevalence of obesity, there has been a dramatic rise of the prevalence of prediabetes and type 2 diabetes among adolescents. Despite that, very little is known about the pathogenesis of these conditions in pediatrics and about how we could detect prediabetes in an early stage in order to prevent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 122 publications
4
45
0
6
Order By: Relevance
“…Prediabetes prevalence decreased as age increased. This observation is supported by previous studies, which showed that insulin resistance increases during puberty and rests to per‐pubertal rates after puberty . The increase in insulin resistance during puberty has been shown to be associated with increased prevalence of prediabetes .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Prediabetes prevalence decreased as age increased. This observation is supported by previous studies, which showed that insulin resistance increases during puberty and rests to per‐pubertal rates after puberty . The increase in insulin resistance during puberty has been shown to be associated with increased prevalence of prediabetes .…”
Section: Discussionsupporting
confidence: 86%
“…Prediabetes (intermediate hyperglycemia), a high‐risk state for developing diabetes, is characterized by blood glucose levels that are above the normal but lower than the diabetes diagnostic thresholds . The altered glucose metabolism found in prediabetes can be described as impaired fasting glucose (IFG), impaired glucose tolerance (IGT), elevated glycated hemoglobin A1c (HbA1c), or their combinations . Although these conditions may refer to a distinct pathophysiological states, their abnormalities, in childhood or adulthood, confer increased risk for developing type 2 diabetes mellitus (T2DM) as well as microvascular and macrovascular diseases …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature has shown that the prevalence in the USA was 2–9% based on the WHO criteria and 15–47% based on the ADA criteria [21]. These estimates align with our results; in subgroup analysis we found that the prevalence of prediabetes ranged from 13.3% among females to 24.4% among those who were obese.…”
Section: Discussionsupporting
confidence: 91%